+0  
 
0
286
2
avatar

2.[3-2.(2-6)]+1 = ?

Guest Sep 30, 2017
 #1
avatar+771 
0

\(2.[3-2.(2-6)]+1 = ?\)

I do not see how this problem is possible as 2-6=-4 and a decimal cannot be negative.

AdamTaurus  Sep 30, 2017
 #2
avatar
0

Simplify the following:
2 (-2 (2 - 6) + 3) + 1

2 - 6 = -4:
2 (3 - 2-4) + 1

-2 (-4) = 8:
2 (8 + 3) + 1

3 + 8 = 11:
2×11 + 1

2×11 = 22:
22 + 1 = 23

Guest Oct 1, 2017

19 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.